Din, Dindar, Dindarlık: Özeleştirel Bir Değerlendirme - Bilgin, Abdülcelil (Muş Alparslan Üniversitesi, 2014)
The fact of religion and religiousness determines systems of life for religious people. The duty of religious people is to live in accordance with his/her religion. The religiousness of the follower of different religions or how they are religious people is a questionable case. To this article, many of relgious’ attitude and behaviors are not suitable for religion. This situtation brings about the misunderstanding of religions.

Din ve dindarlık olgusu, dindar için bir yaşam manzumesi belirler. Dindara düşen, bağlı bulunduğu dinin ilkelerine göre yaşamaktır. Farklı dinlere bağlı dindarların dindarlıkları yahut ne kadar dindar oldukları tartışılması gereken bir konudur. Bu makaleye göre, dindarların çoğunun tutum ve davranışı dindarca değildir. Bu durum, dinlerin yanlış anlaşılmasına neden olmaktadır.
Religion, Religious, Religiousness: a Self-Critical Evaluation
anemon
Keywords: Religion; Religious; Religiousness; anahtar kavramlar: Din; Dindar; Dindarlık